고추의 카로티노이드 함량 분석을 위한 신속･간편 마이크로플레이트법 - 홍순철(Sun Chul Hong); 한정헌(Jung-Heon Han); 이준대(Jundae Lee); 안율균(Yul Kyun Ahn); 양은영(Eun-Young Yang); 채수영(Soo Young Chae); 김수(Su Kim); 윤재복(Jae Bok Yoon) (Weon'ye gwahag gi'sulji, 2013)
In this study, we aimed to develop a simple analysis method for measuring the carotenoids content of pepper powder. A 96-wells polystyrene microplate and an ELISA reader were used for analysis. Although ELISA reader with 450 nm filter was applicable to measure carotenoid contents, the surface of microplates were degenerated by acetone used for carotenoids extraction. However, ten-folded dilute of the color extract with methanol did not affect the surface of polystyrene microplate and components of the color extract could be successfully measured by a ELISA reader, showing a high corelation with ASTA-20.1 method. In addition, this method uses 10 fold less acetone than ASTA-20.1 method resulting less acetone waste. The microplate method using ELISA reader has potential power for analyzing a large number of samples which may be very useful to the practical breeding program for high-colored peppers. 본 연구에서는 폴리스틸렌 재질의 96-well 마이크로플레이트와 ELISA 판독기를 이용하여 고추의 카로티노이드 함량을 간편하게 분석할 수 있는 방법을 개발하고자 하였다. 분광광도계를 이용하지 않고 450nm 필터가 장착된 ELISA 판독기로도 카로티노이드 분석이 가능하였으나, 카로티노이드 추출 시 사용하는 아세톤으로 인해 마이크로플레이트의 표면이 불투명하게 변색되었다. 그러나 아세톤 색소추출물을 메탄올로 10배 희석한 용액을 사용할 경우, 플레이트 표면과 용액 내 카로티노이드 성분의 변화 없이 카로티노이드 측정이 가능하였고, ASTA-20.1법으로 측정된 결과와도 높은 상관관계를 보였다. 한편, 카로티노이드 추출 조건으로는 고춧가루 0.1g을 아세톤 10mL에 첨가하고 실온에서 4시간 동안 교반하는 것이 적합하였다. 본 실험의 ELISA 판독기를 이용한 색소분석법(Microplate법으로 명명)은 대량의 시료를 처리할 수 있을 뿐만 아니라 아세톤 폐액의 발생량을 ASTA-20.1법의 1/10 수준으로 줄일 수 있어 실제 고추 육종에서 고색소 계통을 선발할 때 매우 유용할 것으로 판단된다.